The Concordance of Electronic Health Record Diagnoses and Substance use Self-Reports Among Reproductive Aged Women Enrolled in a Community-Based Addiction Reduction Program - Angela G. Campbell PhD, MPH; Saman Naz PhD, MSPH; Sami Gharbi MS; Joanna Chambers MD; Scott Denne MD; Debra K. Litzelman MD; Sarah E. Wiehe MD, MPH (SAGE Publishing, 2024)
Substance use disorders among reproductive aged women are a major public health issue. There is little work investigating the validity and reliability of electronic health record (EHR) data for measuring substance use in this population. This study examined the concordance of self-reported substance use with clinical diagnoses of substance use, substance abuse and substance use disorder in EHR data. Reproductive age women enrolled in the Community-Based Addiction Reduction (CARE) program were interviewed by peer recovery coaches (PRC) at enrollment. That survey data was linked with EHR data (n = 102). Concordance between self-reported substance use and clinical diagnoses in the EHR was examined for opioids, cannabis/THC, and cocaine. Cohen's kappa, sensitivity, and specificity were calculated. The survey captured a higher number of women who use substances compared to the EHR. The concordance of self-report with EHR diagnosis varied by substance and was higher for opioids (17.6%) relative to cannabis/THC (8.8%), and cocaine (3.0%). Additionally, opioids had higher sensitivity (46.2%) and lower specificity (76.2%) relative to cannabis/THC and cocaine. Survey data collected by PRCs captured more substance use than EHRs, suggesting that EHRs underestimate substance use prevalence. The higher sensitivity and lower specificity of opioids was due to a larger number of women who had a diagnosis of opioid use in the EHR who did not self-report opioid use in the self-report survey relative to cannabis/THC and cocaine. Opioid self-report and diagnosis may be influenced by research setting, question wording, or receipt of medication for opioid use disorder.